2009
DOI: 10.1111/j.1748-1716.2008.01944.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of dystrophin–glycoprotein complex and focal adhesion complex with myosin heavy chain isoforms in rat skeletal muscle

Abstract: Our results support the idea that DGC and FAC are among the factors that explain the fatigue-resistant property not only of slow-type but also of fast-type skeletal muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…2C,D). This differential effect is not completely surprising because previous work has shown that the TA muscle maintains lower levels of β1 integrin than the gastrocnemius muscle (Masuda et al, 2009). These results indicate that short-term treatment with prednisone increases α7A integrin in the muscle of mdx mice.…”
Section: Resultsmentioning
confidence: 68%
“…2C,D). This differential effect is not completely surprising because previous work has shown that the TA muscle maintains lower levels of β1 integrin than the gastrocnemius muscle (Masuda et al, 2009). These results indicate that short-term treatment with prednisone increases α7A integrin in the muscle of mdx mice.…”
Section: Resultsmentioning
confidence: 68%
“…Here we studied the metabolic phenotypes of TA muscle at day 30 postinjury in both genotypes. Two important metabolic enzymes were analyzed in this study, SDH, a marker of aerobic (oxidative) capacity, and ␣-GPD for glycolytic potential (38). The activities of both enzymes in the regenerated myofibers (30 days postinjury) were demonstrated by histochemical reactions and quantified by image analysis.…”
Section: E93mentioning
confidence: 99%
“…Hence, we further assessed the proportion of oxidative muscle fibers in regenerated (day 28 post-notexin injection) TA muscles through assessing SDH activity (22). As expected, there was an increase in SDH activity, as measured through increased SDH staining, in regenerated TA muscles from both WT and PPAR␤/␦-null mice, compared with respective uninjured controls.…”
Section: Loss Of Ppar␤/␦ Does Not Significantly Alter Scar Tissue Formentioning
confidence: 99%
“…Succinate dehydrogenase staining. Succinate dehydrogenase (SDH) activity used to determine the overall oxidative capacity of skeletal muscles was measured using a colorimetric assay, as described by Masuda et al (22). Muscle sections were air-dried for 30 min and incubated in prewarmed PBS buffer containing 50 mM sodium succinate and 0.6 mM nitro blue tetrazolium (Sigma-Aldrich, Singapore) for 25 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%